Systematic Literature Review (SLR) : Kebiasaan Sarapan Pagi Terhadap Tingkat Konsentrasi Belajar Siswa SD - Nihayatur Rohmah; Melinda Khoriyah Ningrum; Syibilla Oktavia Malaka Sari; Anggieta Yesenia Nirwana; Fina Fakhriyah; Erik Aditia Ismaya (Jurnal Mahasiswa Kreatif, 2023)
The purpose of this study was to find out and analyze the relationship between breakfast habits and the learning concentration of elementary school students. The method used in this study is the systematic literature review (SLR) method which aims to dig up information about how much research has done on the topic of the effect of breakfast on the level of learning concentration for elementary school students. Systematic literature review is a technique that systematically examines research on a particular topic by identifying, assessing, selecting, and compiling questions that will be specifically discussed according to predetermined criteria, based on previous research that is of high quality and relevant to the question under study. Based on the results, it was shown that of the four journals that had been analyzed, two journals did not have a significant relationship and the other two journals had a significant relationship between breakfast habits and the learning concentration of elementary school students.